Secondary Adrenal Insufficiency and Growth Hormone Deficiency in Patients with Fibromyalgia - Gruber LM; Nanda S; Nippoldt T; Chang AY; Bancos I (Journal of Pain Research, 2021)
Lucinda M Gruber,1 Sanjeev Nanda,2 Todd Nippoldt,1 Alice Y Chang,1 Irina Bancos1 1Division of Endocrinology, Diabetes, and Nutrition, Mayo Clinic, Rochester, MN, USA; 2Division of General Internal Medicine, Mayo Clinic, Rochester, MN, USACorrespondence: Irina BancosDivision of Endocrinology, Diabetes, and Nutrition, Mayo Clinic, 200 First Street SW, Rochester, MN, 55905, USATel +1 507-286-1387Fax +1 507-284-5745Email bancos.irina@mayo.eduPurpose: Patients with fibromyalgia (FM) may demonstrate low cortisol concentrations during diagnostic evaluation. However, it remains unclear whether low cortisol reflects underlying pituitary dysfunction. We aimed to determine if a subset of patients with FM have concomitant secondary adrenal insufficiency (SAI) and growth hormone deficiency (GH).Patients and Methods: This is a retrospective study of all patients with FM diagnosed with SAI based on abnormal insulin tolerance test (ITT) between June 2002 and August 2019. Patients were excluded if they had other reasons for SAI. Measurements include cortisol and GH during ITT in all patients, and peak cortisol during cosyntropin stimulation test in a subset of patients.Results: We identified 22 patients (median age of 38 years (range 19– 65), 18 (82%) women) diagnosed with secondary AI based on abnormal ITT (peak median cortisol level of 11 mcg/dL (range 5.4– 17)). Concomitant GH deficiency was diagnosed in 19 (86%) patients. Cosyntropin stimulation test was performed in 14 (64%) patients and was normal in 11 (79%) (peak cortisol ≥ 18 mcg/dL). MRI pituitary imaging was performed in 20 patients and showed no significant pituitary pathology. All patients were started on physiologic glucocorticoid replacement, and 5 patients were started on GH replacement. Of the 13 patients with follow-up, 8 (62%) reported symptom improvement after starting treatment.Conclusion: Patients with FM can have concurrent SAI and GH deficiency. Cosyntropin stimulation test should not be used to exclude SAI in patients with FM. Appropriate glucocorticoid and/or GH replacement may improve symptoms in some patients.Keywords: hypothalamus-pituitary dysfunction, cosyntropin stimulation test, insulin tolerance test